Bazedoxifene Regulates Th17 Immune Response to Ameliorate Experimental Autoimmune myocarditis via Inhibition of STAT3 Activation - Wang, Jing; Liu, Tianshu; Chen, Xiongwen; Jin, Qiaofeng; Chen, Yihan; Zhang, Li; Han, Zhengyang; Chen, Dandan; Li, Yuman; Lv, Qing; Xie, Mingxing (Frontiers in Pharmacology, 2021)
Myocarditis is characteristic as an inflammatory cardiomyopathy, which has no specific treatment. Th17 cells have been proposed to play a prominent role in the pathogenesis of inflammation in myocarditis. Interleukin (IL)-6 mediated signal transducer and activator of transcription 3 (STAT3) signaling is essential for Th17 cells differentiation and related inflammatory cytokines secretion. However, the effect of STAT3 inhibition by Bazedoxifene on Th17 immune response during myocarditis was still unknown. Experimental autoimmune myocarditis (EAM) in mice model has been used to mimic the inflammatory heart disease in clinic. Bazedoxifene was administrated orally in mice to investigate the effect on cardiac inflammation. The proportion of Th17 cells and related inflammatory factors were significantly elevated in splenic CD4+ T cells at day 14 and in the heart infiltrating cells at day 21 in EAM mice, which were reduced by the inhibition of STAT3 with Bazedoxifene treatment. In addition, inhibition of STAT3 phosphorylation by Bazedoxifene could increase autophagy in polarized Th17 cells. Bazedoxifene could ameliorate cardiac inflammation and injury. This may provide a promising therapeutic strategy for the treatment of autoimmune myocarditis.